Selecting the house-of-quality-based energy investment policies for the sustainable emerging economies - Tang, Ziyuan; Dinçer, Hasan (MDPI AG, 2019)
The purpose of the study is to evaluate the sustainable energy investments based on house of quality. For that, a hybrid decision-making approach to interval type 2 (IT2) fuzzy sets under the hesitancy is proposed. The novelties of the study are to construct an integrated IT2-based modelling and a set of dimensions and criteria for the sustainable energy investments for the emerging countries. The DEMATEL method is used for weighting the customer expectations of sustainable energy investments. The TOPSIS method is applied for ranking the house-of-quality-based investment policies with the technical requirements for the emerging economies. The results show that the capacity issue of energy industry is the most prominent issue for the technical requirements of energy investments. However, it is concluded that increasing communication with the capacity facilities is the most valuable strategy based on the house of quality evaluation. The results are also discussed for further studies and sustainable policies.
Keywords: DEMATEL; Emerging Economies; Hesitancy; House of Quality; Interval Type-2 Fuzzy Sets; Sustainable Energy Investments; TOPSIS